The use of nouns by deaf students and students with cochlear implant - Bojana Globačnik (University of Maribor Press, 2017)
Cochlear implants have fundamentally changed the rehabilitation and education of deaf people, particularly children. Early operations in children make parents justifiably hopeful that a successful early surgery and hearing and speech rehabilitation may help their child make up their speech and language deficit by the time they enter school. The article provides an analysis of the use of nouns in sentences by a group of deaf students and a group of students with cochlear implants. The two groups were found to be quite equal in terms of their knowledge of the use of nouns. Out of all the age brackets, best results were achieved by students with cochlear implants in the second bracket (10-12 years old), while deaf students without cochlear implants in the third bracket (12-16 years old) achieved better results in tasks involving the nominative case in plural and other cases in the singular grammatical number than students with cochlear implants. The study showed that learning grammar is a difficult and gradual process for deaf students.